27. graph the linear equation
Let's start by replacing x = 0
when x = 0, then y = -2
![\begin{gathered} 0-3y=6 \\ -3y=6 \\ -(3y)/(-3)=(6)/(-3) \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/il8gr5anmht0uf7rha17h9vnivgssyrs2v.png)
so, our first point is (0 , -2)
now, our second point is when y = 0
when, y = 0 , then x = 6
![\begin{gathered} x-3\cdot0=6 \\ x-0=6 \\ x=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bwivpywu3xyshy76huqxpak3rmco43nweg.png)
so, the second point is ( 6 , 0 )
finally, we must draw these two points on the graph and join them with a straight line.